Compact genetic algorithm for designing LCL filter - Sarnthoy, Puriwat; Kaitwanidvilai, Somyot (My University, 2013)
The attenuation of harmonic of LCL filter is better than that of LC filter; thus, this paper focuses on the design of LCL filter. Compact Genetic Algorithm (cGA) is adopted for designing this filter to solve the problem of difficulty of LCL filter design stage. In this paper, three artificial intelligent techniques, Genetic Algorithm, Compact Genetic Algorithm and Particle Swarm Optimization, are adopted to design the filter. Performance of all techniques are investigated and compared.
Keywords: Compact genetic algorithm; Genetic algorithm; LCL filter; Particle swam optimization